(untitled) (Studia Prawnicze / The Legal Studies, 1983)
The notion of workers’ qualifications, taken from legal parlance, is a collective notion denoting all kinds of qualifications occurring in legal acts. In legal. parlance the fundamental meaning have the following notions: professional qualifications, personal and moral ones. The legislator has introduced certain measures in order to facilitate the evaluation of values comprised in the notion of qualifications. However, they do not adequately reflect those values. Not all kinds of qualifications can be evaluated by means of measures. Professional qualifications are a sum of knowledge and skills indispensable and sufficient for the performance of work at a particular workplace. Basic formal measures are: education and practical experience. These two measures are to: I) describe a required level of education and skills for the given workplace or type of work, 2) confirm formally that the worker possesses adequate knowledge and skills. Personal qualifications are of a formal character and their basic measures. are: citizenship, capacity to legal transactions, full public rights. Moral qualifications refer to the worker’s features evaluated on a moral level. These features do not have to be proved as there is a presumption of them which may be shaken by pointing to behaviour which violates moral norms. This type of qualifications cannot be evaluated with formal measures.